KOPOLIMER HIBRID TMSPMA:TEMS SEBAGAI MATRIKS IONIK PADA SEL SURYA TERSENSITISASI DYE - Aprilia, Annisa; Arsyad, Waode Sukmawati; Lamuda, R. N.; Fitrilawati, Fitrilawati; Syakir, Norman; Hidayat, Rahmat (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Three types of electrolyte on dye sensitized solar cell (DSSC) are liquid, solid state, and quasi-solid phase electrolytes. Among these electrolytes quasi-solid phase was expected could be handle some of disadvantages both of liquid and solid state phase on device peformance related to leakage (for liquid phase) and low ionic diffusion (for solid state phase). In conventional DSSC using liquid electrolyte a better efficiency can achieved by high ionic mobility but it is easy to leak leading to lower durabilty performance. In order to enhance durability, many researcher were change the liquid phase by solid state or quasi solid as its electrolyte. This research also try to study the effect of quasi solid electrolyte based on polyetylene glicol modified by hybrid copolymer precursor TMSPMA: TEMS (3:1) as a matrix for ionic liquid. This kind electrolyte is called as polymer gel electrolyte (PGE). Impedance characteristics for PGE was carried out to study electrical characteristics and subsequently applied on solar cell device with structure FTO/ TiO2 / Ru-dye/ PGE / Pt / FTO. Solar cell device with PGE that consist both of polyetylen glicol and copolymer TMSPMA:TEMS have an efficiency of 3.65% under light source Pin= 0.365 mW/cm2 irradiation with short-circuit current density of 3.7 mA/cm2 and open circuit voltage of 0.56 volt was obtained. Keywords: hybrid copolymer, ionic liquid, polymer gel electrolyte, impedance spectroscopy.